Novel insights related to the rise of KPC-producing Enterobacter cloacae complex strains within the nosocomial niche - Knecht, Camila A.; García Allende, Natalia; Álvarez, Verónica E.; Prack McCormick, Barbara; Massó, Mariana G.; Piekar, María; Campos, Josefina; Fox, Bárbara; Camicia, Gabriela; Gambino, Anahí S.; Leguina, Ana Carolina del Valle; Donis, Nicolás; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
According to the World Health Organization, carbapenem-resistant Enterobacteriaceae (CRE) belong to the highest priority group for the development of new antibiotics. Argentina-WHONET data showed that Gram-negative resistance frequencies to imipenem have been increasing since 2010 mostly in two CRE bacteria: Klebsiella pneumoniae and Enterobacter cloacae Complex (ECC). This scenario is mirrored in our hospital. It is known that K. pneumoniae and the ECC coexist in the human body, but little is known about the outcome of these species producing KPC, and colonizing or infecting a patient. We aimed to contribute to the understanding of the rise of the ECC in Argentina, taking as a biological model both a patient colonized with two KPC-producing strains (one Enterobacter hormaechei and one K. pneumoniae) and in vitro competition assays with prevalent KPC-producing ECC (KPC-ECC) versus KPC-producing K. pneumoniae (KPC-Kp) high-risk clones from our institution. A KPC-producing E. hormaechei and later a KPC-Kp strain that colonized a patient shared an identical novel conjugative IncM1 plasmid harboring blaKPC-2. In addition, a total of 19 KPC-ECC and 58 KPC-Kp strains isolated from nosocomial infections revealed that high-risk clones KPC-ECC ST66 and ST78 as well as KPC-Kp ST11 and ST258 were prevalent and selected for competition assays. The competition assays with KCP-ECC ST45, ST66, and ST78 versus KPC-Kp ST11, ST18, and ST258 strains analyzed here showed no statistically significant difference. These assays evidenced that high-risk clones of KPC-ECC and KPC-Kp can coexist in the same hospital environment including the same patient, which explains from an ecological point of view that both species can exchange and share plasmids. These findings offer hints to explain the worldwide rise of KPC-ECC strains based on the ability of some pandemic clones to compete and occupy a certain niche. Taken together, the presence of the same new plasmid and the fitness results that showed that both strains can coexist within the same patient suggest that horizontal genetic transfer of blaKPC-2 within the patient cannot be ruled out. These findings highlight the constant interaction that these two species can keep in the hospital environment, which, in turn, can be related to the spread of KPC.